Average compositions and analyses range for clinopyroxene, olivines, orthopyroxene, and spinel from the MARK area at DSDP Site 45-395A, and ODP Site 153-920 - Indraneel Ghose; Mathilde Cannat; Monique Seyler (PANGAEA, 1996)
Mineral compositions of residual peridotites collected at various locations in the Mid-Atlantic Ridge south of the Kane transform (MARK area) are consistent with generally smaller degrees of melting in the mantle near the large offset Kane transform than near the other, small offset, axial discontinuities in the area. We propose that this transform fault effect is due to along-axis variations in the final depth of melting in the subaxial mantle, reflecting the colder thermal regime of the ridge near the Kane transform. Calculations made with a passive mantle flow regime suggest that these along-axis variations in the final depth of melting would not produce the full range of crustal thickness variations observed in the MARK area seismic record. It is therefore likely that the transform fault effect in the MARK area is combined with other mechanisms capable of producing crustal thickness variations, such as along-axis melt migration, the trapping of part of the magma in a cold mantle root beneath the ridge, or active mantle upwelling.
Supplement to: Ghose, I et al. (1996): Transform fault effect on mantle melting in the MARK area (Mid-Atlantic Ridge south of the Kane transform). Geology, 24(12), 1139-1142, https://doi.org/10.1130/0091-7613(1996)024%3C1139:TFEOMM%3E2.3.CO;2